Substance P radiolabeled with 68Ga as a novel-imaging agent for increased Neurokinin-1 Receptor availability in chronic pain disorders - Sathekge, Mike Machaba (University of Pretoria, 2020)
Thesis (PhD (Medical Nuclear Science))--University of Pretoria, 2019.